Developing organization structure of retail enterprises (on the example of the Czech Republic) - Aleksandr L. Bobkov; Igor V. Denisov; Oksana V. Kuchmaeva (Статистика и экономика)
The goal of the research is to prove repetitiveness of changes in the organization structure of commercial enterprises. With regard to the goals of the research, such scientifically well-known paired notions as vertical and horizontal; high and flat; mechanical and organic can be considered as two basic types of organizational structures. The authors’ hypothesis is that these two types of structures – consequent and parallel – replace each other dialectically, and change qualitatively in the process of enterprises growth, but, at the same time, they maintain their constitutive properties at each level of organizations development.The retail sector was chosen as the object of analysis, since the generalized organizational structure in it is characterized by separate sales outlets, which makes it possible to conduct statistical processing of data. In this context, enterprises of similar size (in terms of number of employees and sales volume) and having similar (consequent or parallel) organizational structures can make groups that form the aggregate of commercial organizations. Cluster analysis is a generally accepted method of defining groups joining objects that are homogeneous with respect to certain criteria. Cluster analysis is the means of exploratory analysis, meant for natural clustering of the initial data set into groups. The IBM SPSS Statistics software was used for defining clusters.The analysis was conducted according to the data of the Czech Republic retail enterprises. The economy of this Central-European country was chosen, because, on the one hand, it is a part of the common market of the United Europe, and, on the other hand, it preserves its national currency. The research data were obtained from the database of Albertina Gold Edition of Bisnode Česká republika, a.s., including enterprises of all the sectors. 1695 retail organizations of all sizes were chosen from the total trade organizations for the research.As a result of the conducted analysis, six clusters were distinguished. When analyzing the average values of the variables in these clusters, they can be classified into four groups. The first group includes 1 105 small trade organizations with the fewest employees (in average, 5.4 people) and representing mainly retail traders or separate small shops. The second group (491 organizations) includes retail chains of small shops. The third group (70 organizations) includes quite large separate stores (supermarkets). In addition, the fourth group (29 organizations) includes large retail store chains (the average number of employees – more than 200, the average number of outlets – more than 23).Overall, the results of the conducted cluster analysis prove the suggested hypothesis. But, of course, the given research should be considered only as the first step, and a more convincing confirmation of alternating consequent and parallel organizational structures requires a more detailed study, including the analysis of certain organizations’ structure. Nevertheless, the obtained results allow suggesting, that the common scheme of retail organizations evolution can be represented as a universal one, since the underlying approaches can be used taking into account the necessary peculiarities for retail organizations of any country with a market economy or a separate region.